Peningkatan Kehidupan Religius Masyarakat Melalui Gerakan Pemuda Masjid Al-Ikhlas Kecamatan Sei Rampah Kabupaten Serdang Bedagai - Riko Ramadhan; Nikmah Royani Harahap; Ade Rahman Matondang (Fakultas Ilmu Pendidikan Universitas Pahlawan Tuanku Tambusai, 2026)
This study aims to analyze the contribution of the Youth Mosque Movement at Al-Ikhlas Mosque in enhancing the religious life of the community in Sei Rampah District, Serdang Bedagai Regency. The research uses a descriptive qualitative approach with data collection techniques including interviews, observation, and documentation. The results show that youth mosque activities such as millennial Islamic studies, mobile Qur’an recitations, leadership training, and social actions significantly contribute to fostering religious enthusiasm within the community. The collaboration between mosque youth and the Mosque Prosperity Board (BKM) is a key factor in ensuring the effectiveness of religious programs. However, several obstacles such as limited funding, fluctuating participation, and the negative influence of social media were also found. In conclusion, the Youth Mosque Movement plays a strategic role as an agent of social and religious transformation within the community, though it still requires structural support and institutional capacity strengthening